Strategi Guru Tahfizh dalam Memotivasi Peserta Didik Menghafal al-Qur’an di SD Semen Padang - Ulfa Rahmi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
The main problem of this study is about the strategy of tahfiz teachers in motivating students memorizing the Qur'an at Semen Padang Elementary School, first the tahfiz teacher strategy in motivating students from social factors, the Second Tahfiz teacher strategy in motivating students from non-social factors. The purpose of the research is to reveal and analyze the strategy of tahfiz teachers in motivating students to memorize the Qur'an at Semen Padang Elementary School. This research is field risearch using descriptive qualitative research methods. The results of the study that the authors found: First; Guru Tahfiz's strategy in motivating students from social factors in memorizing the Qur'an at Semen Padang Elementary School focuses more on motivating by giving advice and encouragement. Second: the strategy of tahfiz teachers in motivating students from non-social factors in memorizing the Qur'an at Semen Padang Elementary School was initially encouraged by the motivation of Ekstrensik because of the school rules, namum during the tahfiz process lived the more days students became aware of the importance of memorizing the Qur'an.